Effect of steam treatment on the characteristics of oil palm empty fruit bunch and its biocomposite - N. I. A., A. Nordin; A. M., Bujang; Jun Haslinda, Shariffuddin (2018)
The amount of wasted product from petroleum-based plastic in landfill has increased and currently, it lead to the environmental problem because it is not easily to degrade. Biocomposite is an alternative material that can be produced to reduce the usage of petroleum-based plastic [1]. The objective of this study is to determine the properties of biocomposite prepared from steam treated oil palm empty fruit bunch (EFB) with polypropylene (PP).